Biginelli Reaction-Carboxylic Acids as Catalysts - Noreen, Sadia; Perveen, Saima; Naeem Khan, Muhammad; Nazeer, Areesha; Ain Khan, Misbahul; Ali Munawar, Munawar; Babar, Rabia; Suhail, Farah; Azad, Muhammad; M.R. Bernardino, Alice; et al. (Asian Journal of Chemistry, 2013)
Mono and dicarboxylic acids were found to be excellent catalysts for the synthesis of dihydropyrimidones/thiones. These are presented as alternate and cheap catalysts for the multicomponent reactions.